2018
DOI: 10.1038/s41416-018-0270-z
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tumours of different histologic type and clinical stage induce similar changes in lipid metabolism

Abstract: Background Previous results obtained from serum samples of late-stage, high-grade serous ovarian carcinoma patients showed large alterations in lipid metabolism. To validate and extend the results, we studied lipidomic changes in early-stage ovarian tumours. In addition to serous ovarian cancer, we investigated whether these changes occur in mucinous and endometrioid histological subtypes as well. Methods Altogether, 354 serum or plasma samples were collected from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 38 publications
8
49
0
Order By: Relevance
“…But we observed that about 30% of differentially expressed proteins between 2 cell lines were participated in metabolic process. Interestingly, we also found lipoprotein lipase, a crucial node in the management of plasma lipid levels by promoting hydrolytic cleavage of the triglyceride core of lipoproteins, was rise significantly in SKOV-3 derived exosomes, this might be the reason for the plasma lipid species variation in malignant or borderline ovarian tumors, and benign pathology [28,37].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…But we observed that about 30% of differentially expressed proteins between 2 cell lines were participated in metabolic process. Interestingly, we also found lipoprotein lipase, a crucial node in the management of plasma lipid levels by promoting hydrolytic cleavage of the triglyceride core of lipoproteins, was rise significantly in SKOV-3 derived exosomes, this might be the reason for the plasma lipid species variation in malignant or borderline ovarian tumors, and benign pathology [28,37].…”
Section: Discussionmentioning
confidence: 66%
“…It is not clear why this is the case, it is possible that the exosomal steroid concentration is cell type dependent and/ or depends on the transfer information packaged by the exosome-secreting cells [14]. Unfortunately, no similar results were found in EOC patient's serum or plasma samples [37]. This may be due to the complicated sources of lipid composition in serum or plasma, of which only a minority of lipid metabolic changes due to ovarian cancer, therefore focuses on the exosomes can show the advantages: the tumor cells secrete exosomes exhaustedly, most exosomes in peripheral blood are tumor derived, and can better reflect the lipid metabolic disorder of tumor, thus supporting the early diagnosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that lipid metabolism disorders may represent important metabolic markers for cancer cells in general. Metabolic reprogramming, including changes in lipid metabolism, can occur in tumor cells and the tumor microenvironment and has impact on the growth, proliferation, invasion and metastasis of cancer cells [10][11][12][13]. Braicu et al [14] conducted a comprehensive lipidomics analysis on the serum samples of 147 EOC patients and 98 control subjects with benign ovarian tumors or non-tumorous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the signal transduction axis of lipid metabolism can effectively prevent peritoneal metastasis of EOC under experimental circumstances [15]. Niemi et al [10] showed that changes in lipid metabolism can occur in various stages of EOC and can become intensified in a consistent pattern with advanced cancer stages.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even though the source of cell-of-origin and underlying biological mechanisms might differ considerably between the subtypes, common features, e.g., changes of the tumour microenvironment of the peritoneum in response to malignant transformation, are shared, and the most recently identified markers of the chloride intracellular channel (CLIC) protein family, CLIC1 and CLIC4, showed promising potential as serum and tissue biomarkers across all subtypes of EOC [4]. Biomarkers include gene expression products, metabolites, circulating nucleic acids characterised by somatic mutations, and splice variants [5,6,7,8,9,10]. The potential of microRNA signatures in the diagnosis and prognosis of ovarian cancer has been especially described in recent years [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%